Acute Stress Disorder among 2022 Ukrainian war refugees: a cross-sectional study - Kordel, Piotr; Rządeczka, Marcin; Studenna-Skrukwa, Marta; Kwiatkowska-Moskalewicz, Katarzyna; Goncharenko, Olga; Moskalewicz, Marcin (Frontiers in Public Health, 2024)
Introduction Fleeing from war can be terrifying and result in Acute Stress Disorder (ASD), a mental health condition that can occur in the first month after a traumatic event. The study aimed to identify the prevalence of ASD among Ukrainian refugees and identify its risk factors to create a profile of the most vulnerable refugees. Methods This cross-sectional study of 637 Ukrainian war-displaced persons and refugees in 2022 used the Acute Stress Disorder Scale. Results The prevalence of ASD among participants was high (93.5%). Several factors increasing the risk of developing ASD in the sample were identified, e.g., witnessing Russian attacks (OR 2.92, 95% CI 1.26–6.78), insufficient financial resources (OR 3.56, 95% CI 1.61–7.91), and feeling of loneliness in the host country (OR 3.07, 95% CI 1.58–8.69). Pre-existing depression and the death of a close person, among others, were found to significantly (p < 0.05) exacerbate the ASD symptoms. At the same time, neither age, the distance traveled, time spent on fleeing the country, nor the type of companionship during refuge (escaping alone, with children, pets or the older adults) correlate with the severity of symptoms. Conclusion The study shows extreme levels of trauma among Ukrainian war refugees and displaced persons. Knowledge regarding ASD vulnerabilities in the present conflict may facilitate prompt and adequate psychological help. Since ASD can be an antecedent of PTSD and several autoimmune disorders, these results may also serve as a predictor of future challenges for Ukrainian society.